2013
DOI: 10.1007/s00232-013-9618-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Aquaporin Function by Integrating Evolutionary and Functional Analyses

Abstract: Aquaporins (AQPs) are a family of channel proteins, which transport water and/or small solutes across cell membranes. AQPs are present in Bacteria, Eukarya, and Archaea. The classical AQP evolution paradigm explains the inconsistent phylogenetic trees by multiple transfer events and emphasizes that the assignment of orthologous AQPs is not possible, making it difficult to integrate functional information. Recently, a novel phylogenetic framework of eukaryotic AQP evolution showed congruence between eukaryotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 155 publications
7
56
0
Order By: Relevance
“…According to the ar/R filter, NIPs can be further divided into three groups (Rougé and Barre, 2008). Group 1 is characterized by residues W V/I A R with permeability to water, glycerol, lactic acid, ammonia, arsenite, and hydrogen peroxide (Wallace and Roberts, 2004;Rougé and Barre, 2008;Perez Di Giorgio et al, 2014). NIP4;1 and NIP4;2 have the same conserved residues, also for other specificity motifs ( Figure 1B), suggesting similar substrate transport specificity and, thus, possibly, functional redundancy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the ar/R filter, NIPs can be further divided into three groups (Rougé and Barre, 2008). Group 1 is characterized by residues W V/I A R with permeability to water, glycerol, lactic acid, ammonia, arsenite, and hydrogen peroxide (Wallace and Roberts, 2004;Rougé and Barre, 2008;Perez Di Giorgio et al, 2014). NIP4;1 and NIP4;2 have the same conserved residues, also for other specificity motifs ( Figure 1B), suggesting similar substrate transport specificity and, thus, possibly, functional redundancy.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably due to the expression of other pollen AQPs (TIP5;1, TIP1;3, SIP1;1, SIP2;1, PIP2;8, TIP1;1, NIP2;1, and NIP7;1; Supplemental Figure 2) apart from NIP4;1 and NIP4;2, which may have some functional redundancy masking more pronounced phenotypes. TIP5;1 and TIP1;3 were shown to transport water and urea; SIP1;1, water; TIP1;1, water, urea, arsenite, and H 2 O 2 ; NIP2;1, water, glycerol, and H 2 O 2 ; and NIP7;1, water, glycerol, urea, boron, arsenite, and H 2 O 2 (revised in Perez Di Giorgio et al, 2014). It has been shown that aquaporin mutantassociated phenotypes were mostly observed under nutrient limiting growth conditions Schnurbusch et al, 2010;Li et al, 2011a;Hanaoka et al, 2014;Wudick et al, 2014;Xu et al, 2015), while the nip4;1 and nip4;2 phenotypes described here are under normal growth conditions.…”
Section: Nip4;1 and Nip4;2 Have A Role In Pollen Germination And Pollmentioning
confidence: 99%
See 1 more Smart Citation
“…As the first (transmembrane helices 1 to 3) and the second half (transmembrane helices 4 to 6) of the protein are imperfect repeats of opposite orientation, intragenic tandem duplication of a precursor has been supposed (Reizer et al 1993; for a structural overview, see Perez Di Giorgio et al 2014). The transmembrane helices form an hourglass-like pore (Jung et al 1994) with a central channel that is crossed by water and solute molecules in a single-file line (Gena et al 2011).…”
Section: Structure-based Functional Classification Of Mipsmentioning
confidence: 99%
“…Major intrinsic proteins (MIPs) or aquaporins (AQPs) are synonyms that are often used in literature (Perez Di Giorgio et al 2014). Such proteins have been discovered in all kingdoms, from Archaea and eubacteria to fungi, animals, and plants (Engel and Stahlberg 2002).…”
Section: Major Intrinsic Proteinsmentioning
confidence: 99%